Paternal and maternal support of moderate-to-vigorous physical activity in children on weekdays and weekends: a cross-sectional study - Meijing An; Tianjiao Chen; Qianling Zhou; Jun Ma (BMC, 2021)
Abstract Background Most studies of associations between parental support behaviours for physical activity (PA) and children's moderate-to-vigorous physical activity (MVPA) have been conducted in developed countries, and they have focused on maternal or parental support behaviours. Children's MVPA time (i.e., weekdays vs. weekends) has not been adequately differentiated. This paper investigated the associations of paternal and maternal support behaviours for PA with the proportion of children who met the MVPA recommendations on weekdays and weekends in China. Methods Cross-sectional data of 517 father-child dyads and 1422 mother-child dyads were analysed. The children recorded PA diaries on 7 consecutive days to assess their MVPA time. The father or mother completed a questionnaire concerning their support for children's PA. Multivariate logistic regression was used to investigate the independent effects of paternal and maternal support behaviours for PA on whether children met the MVPA recommendations for weekdays, weekends, and the whole week. Results Significantly fewer children met the MVPA recommendations on weekends (37.8%) than on weekdays (62.8%). Higher paternal (odds ratio [OR] = 1.098, 95% confidence interval [CI]: 1.009-1.195) and maternal (OR = 1.076, 95% CI: 1.021-1.134) total support behaviour scores were associated with higher odds of children meeting the MVPA recommendations on weekends, after controlling for covariates. Paternal PA knowledge-sharing with the child was positively associated with children meeting the MVPA recommendations on weekends (OR = 1.319, 95% CI: 1.055-1.649); it tended to be associated with children meeting the MVPA recommendations on weekdays and throughout the week, although these associations were not statistically significant. Maternal reservation of PA time for the child was positively associated with a higher likelihood of children meeting the MVPA recommendations on weekdays (OR = 1.160, 95% CI: 1.025-1.313), weekends (OR = 1.241, 95% CI: 1.097-1.403), and throughout the week (OR = 1.214, 95% CI: 1.076-1.369). Conclusions Paternal and maternal support behaviours for PA should be enhanced on weekends to increase children's MVPA. Fathers should share PA knowledge with children and mothers should reserve PA time for children every day.